2014
DOI: 10.1186/1476-069x-13-54
|View full text |Cite
|
Sign up to set email alerts
|

A case control study of environmental and occupational exposures associated with methicillin resistant Staphylococcus aureus nasal carriage in patients admitted to a rural tertiary care hospital in a high density swine region

Abstract: BackgroundDistinct strains of methicillin resistant Staphylococcus aureus (MRSA) have been identified on livestock and livestock workers. Industrial food animal production may be an important environmental reservoir for human carriage of these pathogenic bacteria. The objective of this study was to investigate environmental and occupational exposures associated with nasal carriage of MRSA in patients hospitalized at Vidant Medical Center, a tertiary hospital serving a region with intensive livestock production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…Several studies revealed that the density of pigs in farms was associated with LA-MRSA acquisition [ 38 , 39 , 40 ]. The study in Denmark showed that living near pig farms was a risk factor for LA-MRSA carriage [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies revealed that the density of pigs in farms was associated with LA-MRSA acquisition [ 38 , 39 , 40 ]. The study in Denmark showed that living near pig farms was a risk factor for LA-MRSA carriage [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we did not find any typical livestock associated spa types (CC398 or ST9), tetracycline resistance was uncommon, and few isolates were negative for the scn gene. Similarly, studies in North Carolina [ 30 ] and Pennsylvania found that proximity to livestock operations and swine manure application to crop fields is associated with increased odds for MRSA infection [ 31 ]. Yet, in those studies, no typical LA-MRSA spa types were found, and few isolates were scn -negative [ 30 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, studies in North Carolina [ 30 ] and Pennsylvania found that proximity to livestock operations and swine manure application to crop fields is associated with increased odds for MRSA infection [ 31 ]. Yet, in those studies, no typical LA-MRSA spa types were found, and few isolates were scn -negative [ 30 , 32 ]. Our previous results from Iowa, Ohio, and Connecticut have shown that while CC398 is the most common sequence type [ 8 , 9 , 22 ], other genetic types have also been found to colonize swine [ 22 - 24 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, resistance is not confined to nosocomial settings. Environmental strains also encode resistance (Leamer, Clemmons, Jordan, & Pacha, ; Rose et al., ; Rothrock, Hiett, Guard, & Jackson, ) and contribute to life‐threatening community‐acquired infections (Furuya‐Kanamori et al., ; Leamer et al., ; McKenna, ; Schinasi et al., ). Escalating the crisis is the shift of major pharmaceutical companies away from antibiotic discovery and synthesis due to low profitability (Pammolli, Magazzini, & Riccaboni, ; Scannell, Blanckley, Boldon, & Warrington, ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, resistance is not confined to nosocomial settings. Environmental strains also encode resistance (Leamer, Clemmons, Jordan, & Pacha, 2013;Rose et al, 2009;Rothrock, Hiett, Guard, & Jackson, 2016) and contribute to lifethreatening community-acquired infections (Furuya-Kanamori et al, 2015;Leamer et al, 2013;McKenna, 2008;Schinasi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%